Evaluation Of Antimicrobial Activity And Phytochemical Screening Of Ethanolic Extract Of Greater Duckweed, Spirodela Polyrrhiza - BASANTA KUMAR DAS,; DURGA PRASAD DAS,; JYOTIRMAYEE PRADHAN,; BARSHA PRIYADARSHINEE,; IPSITA SAHU,; PRAGYAN ROY,; BIBUDHENDRA KUMAR MISHRA, (International Journal of Pharma and Bio Sciences, 2012)
The phytochemical screening of the various extracts of Spirodela polyrrhiza revealed the presence of alkaloids, steroids, flavonoids and saponins. Fourteen fractions were elucidated from the ethanolic extract using the silica gel column chromatography. Antimicrobial activities of the ethanol and fractions of ethanolic extract of S. polyrrhiza against Gram-negative strains of Aeromonas hydrophila (AH1), Psedomonas putida (ATCC 49128), P. aeruginosa (ATCC 35072), P. fluorescens (PF1), Vibrio parahaemolyticus (ATCC 17802), V. Alginolyticus (ATCC 17749), E. coli (EC1) and Gram-positive strain of Staphylococcus aureus (ATCC 6538) and fungal pathogens, Candida albicans and Saprolegnia parasitica were done by disc diffusion methods showed that the extract possess broad spectrum of activity against the test organisms with diameter of zones of inhibition ranging from 9.0 - 16.0 mm. The minimum inhibitory concentration (MIC) of the extract against the test organisms were found to fall between 30 - 200 µg/ml.